Nanostructural glass composite coatings - Kharchenko, S.D.; Kharchenko, O.V. (Problems of Tribology, 2022)
The results of the study of glass-composite nanostructured self-lubricating coatings are presented. The developed glass composite is an antifriction material with an ultrafine structure. The structural components of these coatings significantly affect the graphitization process and provide an antifriction surface layer of α-graphite. The formation of this layer makes it possible to significantly minimize the contact parameters in the friction region. The developed antifriction nanostructured glass-ceramic self-lubricating coatings containing magnesium carbide and structural components that promote surface graphitization do not contain expensive and scarce components, meet environmental safety requirements, and have high performance characteristics. A significant effect of aluminoborosilicate in the form of a glass phase on the tribological properties of coatings is noted. An increase in adhesive strength is achieved by forming a surface layer of glassy sodium silicate. Using X-ray phase analysis, it was found that the intercalating elements in the subsurface zone-graphite system at the initial stage of the process were Mg2+, Al3+, Cu2+ ions, which randomly penetrated into the interlayer space of the graphite matrix. At sliding speeds of more than 3.0 m/s, intercalates of binary molecular compounds of these elements with oxygen were found in the layered system of graphite. Their intercalation is accompanied by a sequence of repetitive stages, which are reversible with a change in tribological parameters and are characterized by a specific transformation of the structure and, above all, by an increase in the distance between layers due to the influence of various types of interlayer defects and the introduction of intercalants. The presence of near-surface particles in the graphite layer does not affect the tribotechnical characteristics of the coatings. The developed glass-composite nanostructured self-lubricating coatings have high antifriction characteristics throughout the entire load-speed range